Employees, Pensions, and Governance in Chapter 11 - David A. Skeel Jr. (Washington University Law Quarterly, 2004)
In Bankruptcy and Workers: Risks, Compensation and Pension Contracts, the excellent Article that anchors the section of this symposium concerning the treatment of employees in bankruptcy, Richard Ippolito explores the full range of pension risks that an employee faces in the event of a financial downturn. Focusing principally on defined benefit pension plans—that is, pensions that promise employees a specified return when they retire—Ippolito suggests that the best justification for protecting part but not all of an employee’s benefits if the employer later terminates its pension plan is strategic: if employees face a risk of loss in the event of termination, they are less likely to attempt to divert value from the company’s shareholders. Ippolito explores in detail the pension risk faced by employees at various stages of their career, pointing out that mid-career employees have the most to lose if their employer terminates a defined benefit plan. He also offers a compelling explanation for the dramatic shift away from defined benefit plans to the defined contribution approach, and describes ways that defined contribution plans could replicate the risk profile of the traditional defined benefit pension. Part I of this Comment describes the treatment of individual employees who are laid off shortly before or after a company files for Chapter 11 and contrasts this with the approach taken in France and other European countries. Part II considers the employees that a firm wishes to retain and the efforts firms have made to give them special treatment. Part III focuses on pensions, describing the defined contribution revolution and bankruptcy’s effect on these and defined benefit plans. Part IV explores the status of collective bargaining agreements, an issue that flared up in the 1980s and has been profoundly affected by recent developments in the governance of Chapter 11 cases. Part V is a brief conclusion.
Keywords: Pensions; Corporate bankruptcy; Collective bargaining; Layoffs; Bankruptcy reorganization; Corporate governance; Workers' compensation